Barriers in Instructional Technology Integration in Teachers in Social Studies at Jordan Elementary School - Smadi, Mohammad Abed-Latif Mohammad; Mohammad, Abdul Halim; Rahman, Faizahani Ab (Universitas Muhammadiyah Sidoarjo, 2020)
The purpose of this paper is to identify the importance of using Instructional Technology(IT) in teaching social studies in elementary schools in Jordan. This paper explores theobstacles faced by female teachers in teaching social lessons in classrooms in Jordan.Lack of competence to apply technology to teach social lessons in class. is a problemthat occurs among female teachers in Jordan. Those with little experience find it difficultto apply because of the unavailability of equipment. the results of the discussion of thispaper can teach teachers to integrate technology into the education system, integrate ITinto classrooms and integrate IT in teaching social studies in Jordan elementary schoolsto improve the performance of female social studies teachers.